BIO-CONTROL OF MULTIPLE DRUG-RESISTANT UROPATHOGENS USING MEDICINAL PLANT EXTRACTS - CHAUDHARY, VIGI; RK, RAGHUVANSHI; CHAUDHARY, NAVEEN; SHARMA, GAURAV (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was conducted to evaluate the potential of some medicinal plants used in Ayurveda in treating multiple drug-resistant human pathogens causing urinary tract infections (UTIs). Methods: Dried parts of six medicinal plants used in Ayurveda for treating UTI were Soxhlet extracted, and the extract was concentrated in vacuo. Various concentrations of the extract were tested for antimicrobial activity against three clinical isolates of multiple drug-resistant bacteria causing UTI. Results: Preliminary results showed the promising antibacterial effect of plant extracts. Escherichia coli, the most common pathogen associated with UTI, was susceptible to aqueous extracts of all the six medicinal plants. Conclusion: This study concluded that the medicinal plants used in Ayurveda to treat UTIs are effective against multiple drug-resistant uropathogens. Further study in this regard may lead to the identification of novel antimicrobial agent for treating multiple drug-resistant urinary tract pathogens.